Research on evolutionary game of low-carbon logistics in two-level supply chain under carbon tax policy - Yong Wang; Huajun Luo; Xiaoyu Zhang; Yani Li; Suo Yang; Qian Lu; Lihui Wang (Sustainable Futures)
Aiming at the problem of low carbon emission reduction in the sustainable development of the logistics industry, this study adopts the research method combining game theory and dynamic system analysis. A tripartite evolutionary game model including the logistics company, the manufacturer, and the government is constructed, and the strategy choice and mutual influence of each participant in the process of low-carbon emission reduction are discussed. At last, MATLAB software is used to simulate the model. By adjusting the values of different parameters, the process and results of the dynamic evolution of the system are displayed intuitively. It was found that the government's sound penalty and subsidy policy plays a key role in promoting the evolution of the manufacturer and the logistics company to adopt low-carbon strategies. Specifically, higher subsidies and moderate penalties can encourage enterprises to take low-carbon measures and promote the system's evolution to a low-carbon and stable equilibrium point. These conclusions help the logistics company and the manufacturer to identify the key factors and paths of low-carbon development, promote growth in the direction of low-carbon, green, and sustainable development, and provide theoretical support and empirical basis for the government to formulate and improve relevant policies on carbon emission reduction, and improve the effectiveness and pertinency of policies.